Senescence-Associated Secretory Phenotype as a Key Driver of Intestinal Aging: A Narrative Review - Yustina Nuke Ardiyan; Johana Puspasari Dwi Pratiwi (CV. Publikasi Indonesia, 2026)
Population aging is accompanied by progressive deterioration of intestinal structure and function, leading to impaired epithelial regeneration, increased intestinal permeability, chronic inflammation, and gut microbiota dysbiosis. Emerging evidence has identified the senescence-associated secretory phenotype (SASP) as a major mediator linking cellular senescence to intestinal aging; however, current evidence remains fragmented. This narrative review aimed to synthesize recent findings regarding the role of SASP in intestinal aging, with particular emphasis on its molecular mechanisms, biological consequences, and potential therapeutic strategies. A literature search was conducted in PubMed using the keywords (